International Perspectives on Income Support for Families with Children - Shelley Phipps (Luxembourg Income Study (LIS), 1993)
Employs micro-data from LIS to provide an institutional and statistical survey of programs which provide income support for families with children in six countries. One of the strengths of this paper is that not only are underlying philosophies defined and compared but macro variables, gained from the Institutional Data Base at LIS, are also used for overall comparisons.
Keywords: 330